Informality and contributory and non-contributory programmes: recent reforms of the social protection system in Uruguay - Cruces, Guillermo Antonio (2013)
Several countries in Latin America are expanding their social-protection systems. There is an on-going debate about the trade-offs implied by these expansions, and by the resulting interactions between contributory and noncontributory programmes with informality in the labour market. This article analyses the potential incentive effects for formal and informal employment from a set of social-protection reforms implemented in Uruguay in the 1990s and 2000s. It presents empirical evidence of the expansion of health insurance to formal workers’ dependants, and finds that this reform significantly increased formal employment. Finally, it discusses possible alternatives to extend social-protection systems while maintaining incentives for formal work in Latin America’s labour markets.